Plasma small extracellular vesicles as biomarkers in neurodegenerative dementias: focusing on microglial enrichment in dementia with Lewy bodies - Isik, Fatma Busra (2025)
There is an urgent clinical need for identifying blood-based biomarkers that can aid distinguishing between the two most common neurodegenerative dementias, AD and DLB. Advancing our understanding of its molecular pathogenesis is essential for identifying novel biomarkers and therapeutic targets for them. Extracellular vesicles (EV) are cell-derived vesicles with lipid bilayer membrane which carry biologically active proteins, lipids and nucleic acids including messenger RNA (mRNA) and small non-coding RNAs from their cells of origin. Because of their potential for transferring biological information, and ability for cell-to-cell communication, EV can be utilised as a tool to develop blood-based biomarkers for differentiating DLB from AD.